1973
DOI: 10.1017/s0022172400023019
|View full text |Cite
|
Sign up to set email alerts
|

Skin tests with influenza virus

Abstract: SUMMARYSkin reactions have been produced in normal subjects by the injection of highly purified influenza A and B viruses. The reactions reached a maximum at 24-48hr. and the histological pattern was compatible with a delayed hypersensitivity reaction. There was no close relation between skin test results and circulating antibodies. Twenty-seven subjects were challenged intranasally with attenuated influenza A (H3N2): 5 of 14 skin-test-negative subjects were infected, but none of 13 skin-test-positive subjects. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Therefore, a toxic agent different from any of the toxic substances mentioned in this report should be looked for , provided that the local reactions are not of immunological nature. There is a report suggesting that a delayed hypersensitivity reaction might be caused by a component(s) of influenza virus itself (Habershon et al, 1973). APPENDIX By use of the data (see the attached figure) borrowed from Dr. S. Kanoh, the regression coefficient.of the temperature rise in the rabbit by influenza virus against log dose was calculated to be 1.1541.…”
Section: Effects O F Heat and Formaldehyde Treatments On Early Leukopmentioning
confidence: 99%
“…Therefore, a toxic agent different from any of the toxic substances mentioned in this report should be looked for , provided that the local reactions are not of immunological nature. There is a report suggesting that a delayed hypersensitivity reaction might be caused by a component(s) of influenza virus itself (Habershon et al, 1973). APPENDIX By use of the data (see the attached figure) borrowed from Dr. S. Kanoh, the regression coefficient.of the temperature rise in the rabbit by influenza virus against log dose was calculated to be 1.1541.…”
Section: Effects O F Heat and Formaldehyde Treatments On Early Leukopmentioning
confidence: 99%
“…In previous clinical trials with other live influenza virus vaccines, low level transmission was reported between close contacts (McDonald et al 1962), but could not be demonstrated between volunteers in closed communities (Davenport et al 1971;Habershon et al 1973;Lamy et al 1973). In a trial of 'Alice' live influenza vaccine carried out at The Centre for Disease Control, Atlanta, Georgia, no evidence of transmission was observed in wives of 31 live virus vaccinees who had received doses of vaccine similar to those employed in this study (R. J. Rubin, G. R. Noble, L. Corey, D. Brandling-Bennett, H. Kaye, M. T. Coleman, W. J.…”
mentioning
confidence: 96%
“…However, there is remarkably little information on the possible role of the other major aspect of cellmediated immunity, delayed-type hypersensitivity (DTH), although DTH to influenza virus has been demonstrated in natural human infection [7,81 and in mice injected with matrix protein incorporated in Freund's complete adjuvant [9].…”
Section: [I 23731mentioning
confidence: 99%